UPAYA MENINGKATKAN HASIL BELAJAR PKN DENGAN MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE TGT (TEAMS GAMES TOURNAMENS) - Jumiati (Jurnal PGSD Musi, 2018)
This research is a classroom action research effort titled PKN improve learning outcomes by using cooperative learning model tournamens teams games (TGT) grade V SD 24 Negeri Betung. The purpose of this research is to improve student learning outcomes grade V SD 24 Negeri Betung through cooperative learning model tgt. The research subjects were students in grade grade V SD 24 Negeri Betung which has 21 students, consisting of 11 men and 10 women. The success of the study were analyzed based mastery learning students who obtained the value of the cycle. Otherwise completed in the student learning outcomes when reaching a value of 65 while the class if terdapar otherwise completed 75% of students who scored 65 or more. It can be concluded that the results of PKN learning using cooperative learning model TGT grade V SD 24 Negeri Betung declared the country increased. Therefore, it is suggested that teachers can develop lessons using cooperative model type engingkatkan TGT due to student learning outcomes.